Identity Under Scrutiny: Media Attention and Rule Compliance - Sulin Sardoschau; Giorgio Gulino; Federico Masera (Institute of Labor Economics (IZA), 2025)
How does media coverage of minorities affect their rule compliance? Using data from 800,000 random audits at supermarket self-checkouts in Italy, we show that heightened refugee media coverage reduces under-reporting of items among shoppers born in major refugee-source countries, but not other migrants or natives. The effect is concentrated in the seven days following media exposure and is strongest when coverage is negative or highlights criminality. Results are not driven by changes in customer composition or perceived audit risk. Instead, our findings suggest that public scrutiny prompts minorities to counter negative stereotypes by increasing their compliance.
Keywords: D74; J15; D83; Z10; D72; 330; immigration; refugees; identity; crime; media; threat